PERTANGGUNGJAWABAN HUKUM ATAS PENOLAKAN KLAIM ASURANSI OLEH PT ASURANSI JIWA GENERALI INDONESIA: ANALISIS PUTUSAN NOMOR 149/Pdt.G/2024/PN Medan - Rizki Rizki; Jeskon Amir Nduru; Jeremi Sahputra Ketaren; Lorenzo Law (Jurnal Ilmiah Advokasi, 2026)
This study examines Decision Number 149/Pdt.G/2024/PN Medan concerning a dispute over the rejection of a life insurance claim and its implications for legal protection of policyholders in Indonesia. The research employs a normative juridical method through doctrinal analysis of court decisions, using statutory, conceptual, and case approaches. The statutory approach refers to Law No. 40 of 2014 on Insurance and the Consumer Protection Law, while the conceptual approach is grounded in the principles of pacta sunt servanda and legal protection theory. The findings reveal that the insurer rejected the claim on the grounds of alleged misrepresentation of the insured’s health condition. However, the court found that such grounds were not supported by sufficient evidence and failed to meet the principle of good faith. Consequently, the rejection was deemed a breach of contract that harmed the policyholder. The decision reaffirms that insurance companies bear contractual obligations that must be performed in accordance with legal certainty and consumer protection principles. Furthermore, the ruling reinforces both preventive and repressive legal protection frameworks, as articulated by Philipus M. Hadjon, and highlights the role of the Financial Services Authority (OJK) and the Financial Services Sector Alternative Dispute Resolution Institution (LAPS SJK) in resolving insurance disputes. From a theoretical perspective, this study contributes to the development of insurance law by clarifying standards of proof in claim rejection and strengthening the application of the good faith principle in insurance contracts. This study recommends strengthening regulatory frameworks on policy transparency, optimizing alternative dispute resolution mechanisms, and accelerating the establishment of a Policy Guarantee Institution to enhance legal certainty and protection for life insurance policyholders in Indonesia.Keywords: Life Insurance, Legal Protection, Claim Dispute, Breach of Contract, Good Faith Principle